Purification and characterization of lipase from Bacillus subtilis kubt4 for biodiesel production - Parveen Nadaf; Shridhar Ghagane; Rubeen Dadakalandar Nadaf; Shivasharana Chandrabanda Timmappa (Discover Applied Sciences)
Abstract The synthesis of biodiesel, a vital step in the search for sustainable energy sources, frequently entails costly procedures in which lipases are vital. This research focuses on the purification and characterization of lipase isolated from Bacillus subtilis kubt4, emphasizing its potential application in biodiesel production. The enzyme was purified using chromatographic techniques and characterized for its biochemical properties, substrate specificity, and stability under various conditions. Insights gained underscore its suitability as a biocatalyst for efficient biodiesel synthesis. To determine whether a lipase enzyme produced from Bacillus Subtilis kubt4 (Gene Bank Accession Number SUB3191429) has potential for use in industrial settings, this work focused on its purification and characterization. Three major chromatographic phases composed the enzyme purification procedure, which produced a lipase with a specific activity of 11.64 U/mg protein and a recovery yield of 11.27% after a 7.36-fold purification. SDS‒PAGE analysis revealed a molecular mass of 30 kDa, while MALDI-TOF MS and Mascot search analysis confirmed that the purified protein was a lipase. The characterized lipase exhibited alkaline properties, displaying optimal activity and stability at pH 8.0 and a temperature of 35 °C. The presence of Mg2+ ions significantly enhanced the enzyme activity by 180.21%. Kinetic analysis revealed Vmax and Km values for pNP palmitate of 8.33 M and 1.025 μM/min, respectively. Furthermore, the purified lipase was employed in the transesterification of Pongamia oil for biodiesel production. The biodiesel profile obtained from Pongamia oil demonstrated its suitability and sustainability as a biofuel source. Overall, this work clarifies the possible industrial use of purified lipase from Bacillus Subtilis kubt4 in the manufacturing of premium, eco-friendly biodiesel.